"Diseño de un modelo de gestión para el desarrollo organizacional de la Cooperativa de Ahorro y Crédito "18 de Noviembre" ubicada en la ciudad de Quito (período 2011-2016)". - Taimal Morocho, Viviana Jacqueline (2013)
After the research study conducted an analysis of organizational development theories and management models was conducted to define the most appropriate model to the activities developed by the Cooperative. The General Systems Theory and specifically whether the systemic model is right for institution was determined. The activities developed by the Cooperative were grouped into five departments, thereby allowing for defined for each process, which is documented in the study. For each process a survey was performed and the time it takes each activity was noted.